CODE SWITCHING IN SOCIAL MEDIA - Jon Piter Situmorang; Jojor Christa Sinaga (Muse: Jurnal of Art, 2023)
This article deals with Code Switching in Social Media. The objectives of this research are to find out the kinds and the reasons of using code switching in social media. The sources which used in collecting the data are four social media they are Instagram, Facebook, TikTok and Twitter. This research used the qualitative analysis to carry out the study. The result of the analysis shows that there are three kinds of code switching and five the reasons of doing code switching: they are interjection, to reflect social status, Prestige and trend, lack of vocabulary, and topics. And based on the analysis of the study, it is found that the highest number of the kinds of code switching is intra sentential code switching which attain 48 data. The main reasons of the users in social media doing code switching is prestige and trends which attain 25 data and the most significances used code switching in social media is instagram which attain 29.